Investigation of UV-Visible Absorption Quantum Effects Doped of Norepinephrine, Mg+2 Atom by Using DFT Method - Kebiroglu, Hanifi; Yılmaz, Mücahit (Niyazi BULUT, 2023)
The research focused on investigating and optimizing the interaction of the hormone Norepinephrine (Noradrenaline), which acts as a neurotransmitter, with Mg+2 atoms at the molecular level. To do this, we used GaussView 6.0.16 to generate the molecular structure. Then, it employed Gaussian 09: AS64L-G09RevD.01 program to optimize the molecular structures of Norepinephrine using the DFT method and SDD basis set, and the Mg atom doped molecule using the DFT method and LanL2MB basis set. Various quantum mechanical calculations were conducted on the molecule, including Fourier Transform Infrared spectroscopy (FT-IR), Nuclear Magnetic Resonance Spectroscopy (NMR), HOMO-LUMO structure with the energy level diagram, UV-visible absorption, and density of states (DOS). These calculations provide important insights into the behavior and properties of the Norepinephrine-Mg+2 complex at the molecular level.
Keywords: Classical Physics (Other); Klasik Fizik (Diğer)